2022
DOI: 10.1177/03000605221126378
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic analysis of Langerhans cell histiocytosis in children: a report of 55 cases

Abstract: Objective To explore the value of ultrasonography in the diagnosis and treatment of Langerhans cell histiocytosis (LCH) in children. Method The clinical and imaging features of 55 children with pathologically confirmed LCH were retrospectively analyzed. Results Thirteen patients had bone LCH and 42 had multisystem LCH. Among the 13 cases of bone LCH, 8 cases involving the skull and 2 involving the scapula were characterized by osteolytic bone destruction, 1 case involving the clavicle and 1 involving the iliac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Typically, CCH can be categorized into 3 types: cystic and solid mixed-type, solid mass type, and thick-walled cystic type. [ 8 ] CCH lesions may display diverse surface colors, including red, blue, normal skin color, and brown. Although CCH primarily manifests in the skin of the scalp, face, anterior trunk, and limbs, literature reports suggest its occurrence in the breast as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, CCH can be categorized into 3 types: cystic and solid mixed-type, solid mass type, and thick-walled cystic type. [ 8 ] CCH lesions may display diverse surface colors, including red, blue, normal skin color, and brown. Although CCH primarily manifests in the skin of the scalp, face, anterior trunk, and limbs, literature reports suggest its occurrence in the breast as well.…”
Section: Discussionmentioning
confidence: 99%
“…Although CCH primarily manifests in the skin of the scalp, face, anterior trunk, and limbs, literature reports suggest its occurrence in the breast as well. [ 8 , 9 ] Breast CCH is rare, and some studies have indicated that it may coexist with both eccrine sweat glands and mammary ducts. [ 10 ] When CCH is situated within the mammary duct, its ultrasound appearance manifests as a cystic lesion within the deep breast tissue.…”
Section: Discussionmentioning
confidence: 99%